Estimating oil palm (Elaeis guineensis) production potential using Unmanned Aerial Vehicle - CHARLOQ CHARLOQ; ACHMAD SIDDIK THOHA; ABU YAZID; AGUNG MUAMMAR SIDIQ; OPPIE APRILIA LUBIS (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Charloq, Thoha AS, Yazid A, Sidiq AM, Lubis OA. 2024. Estimating oil palm (Elaeis guineensis) production potential using Unmanned Aerial Vehicle. Biodiversitas 25: 2981-2989. The vast expanse of oil palm (Elaeis guineensis Jacq.) plantations utilized Unmanned Aerial Vehicle (UAV) technology, identified as a suitable tool for mapping the health condition and production potential of oil palm plants. A plant census was conducted to confirm the correct number of plants, utilizing GPS to record each plant's coordinates, assess its health status, and estimate its production potential. This study aimed to estimate oil palm production potential with maximum accuracy using drone technology over a 22.23-hectare plantation. The research method involved drone based mapping of plant numbers and health, thereby estimating the potential production of oil palm. Orthomosaic data processed using Oil Palm Analysis (OPA) software were analyzed and compared with field survey data (plant census) through the Student t test with ? = 5%. In conclusion, from the study of drone/UAV technology based estimation of oil palm (E. guineensis) production potential in the field on an area of 22.23 ha at PT. Eastern Indonesia Bukit Maradja Estate, North Sumatra Province, Indonesia, it can be concluded that the use of drone technology for oil palm production estimation through OPA is highly effective, with no significant discrepancies between drone results and traditional field census methods. This consistency confirms that UAVs are a reliable tool for assessing the production potential of oil palm plantations.